The Geltwood, all lost! The Lightning, all saved! (1876)
Two images of ships in trouble off the S. Aust. coast. On the left the Geltwood sinking in Rivoli Bay in 1876, in the foreground a female figure in Roman-style clothing grieving. Below the image a poem about a ship wreck by Byron. On the right the Lightning ran aground as it neared Adelaide 7 July 1876, in the foreground a female figure point to an urn. Below a poem praising the government for sending lifeboats to save the immigrant passengers and crew.
Condition: good. Large stain upper left.
Inscriptions: "July 15,1876 The Lantern, no. 96" -- above image. Below the Geltwood a poem by Byron, below the Lightning a 4 line poem about the saving of the ships passengers. Artists initials l.r. of each image, "IH" ?
Also available online
Keywords: Lightning (Clipper-ship) .; Geltwood (Ship); Shipwrecks -- South Australia -- Pictorial works